Pengaruh Kinerja Keuangan Likuiditas, Leverage dan Profitabilitas terhadap Financial Distress - Arief, Harefan; Fauzi, Firman; Saratian, Eko Tama Putra; Ashshidiqy, Nurdin; Kolis, David Nabhan (Jurnal Doktor Manajemen (JDM), 2021)
Seeing the declining condition of Indonesia's economy, it touched negative growth because the world economy was also experiencing negative growth due to the Covid-19 pandemic. It is undeniable that every company will be overshadowed by a decline in financial performance which in the end can have an impact on the inability to manage finances so that in this condition if it continues it will cause financial distress. The purpose of this result is to identify and analyze the influence of fundamental factors represented by the ratio using the Ratio Analysis of ROA, DER and Current Ratio in Altman and Zmijewski's Financial Distress Analysis to see the effect of Liquidity, Leverage and Profitability on Financial Distress on mining sector stocks in the Stock Exchange. Indonesian Securities. Data analysis in this study is a oil and gas company on the Indonesia Stock Exchange during 2015-2019. Based on the calculation of ROA, DER and Current Ratio against Altman's Zscore. It can be concluded that the DER ROA variable does not partially affect the Zscore. Variable Current ratio affects to Zscore. The variables ROA, DER and Current Ratio simultaneously affect to Zscore. Then calculate the ROA, DER and Current Ratio to the Zmijewski Value. It can be concluded that the ROA variable partially affects to the Zmijewski value. DER and Current Ratio variables partially have no effect to Zmijewski value. The variables ROA, DER and Current Ratio simultaneously affect to Zmijewski Value.  Keywords: Altman, Financial Distres, Financial Performance, Zmijewski